2009
DOI: 10.1002/adfm.200901169
|View full text |Cite
|
Sign up to set email alerts
|

B–Z DNA Transition Triggered by a Cationic Comb‐Type Copolymer

Abstract: The conformational transition from right‐handed B–DNA to left‐handed Z–DNA—the B–Z transition—has received increased attention recently because of its potential roles in biological systems and its applicability to bionanotechnology. Though the B–Z transition of poly(dG–dC) · poly(dG–dC) is inducible under high salt concentration conditions (over 4 M NaCl) or by addition of multivalent cations, such as hexaamminecobalt(III), no cationic polymer were known to induce the transition. In this study, it is shown by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 37 publications
4
18
1
Order By: Relevance
“…The mechanism behind the diverse effects of monomeric TMA + ion and MPLL-g-Dex multivalent ions are not yet understood. We previously reported that PLL-g-Dex induces B-form to Zform transitions of poly(dG-dC)•poly(dG-dC) dsDNA [23]. Interestingly, changes of the dsDNA conformation by MPLL-g-Dex were not observed in CD measurements (data not shown).…”
Section: Discussioncontrasting
confidence: 57%
“…The mechanism behind the diverse effects of monomeric TMA + ion and MPLL-g-Dex multivalent ions are not yet understood. We previously reported that PLL-g-Dex induces B-form to Zform transitions of poly(dG-dC)•poly(dG-dC) dsDNA [23]. Interestingly, changes of the dsDNA conformation by MPLL-g-Dex were not observed in CD measurements (data not shown).…”
Section: Discussioncontrasting
confidence: 57%
“…US2 was subsequently studied for its detail characterization including binding and melting curve analysis. As indicated previously, two factors are mainly required to trigger B-Z transition, shielding of the electrostatic repulsion from phosphate groups of DNA and reducing water activity in Z-DNA stabilization484950. The preference for B- over Z-DNA has been ascribed to electrostatic repulsion between adjacent phosphate oxygen which are approximately 1 Å closer in the Z-form51.…”
Section: Resultsmentioning
confidence: 82%
“…The Z-DNA peaks of GC-DNA increased after gradually addition of SC-dots (Figure 2C). As the B-Z transition was accompanied by a change in the UV spectrum, a marked hypochromism and bathrochromic shift was also observed (Figure 2D) (17,20). UV spectral change of AT-DNA was also different from GC-DNA, and there was no obvious shift on SC-dots binding (Supplementary Figure S5B).…”
Section: Resultsmentioning
confidence: 90%